112k views
4 votes
When you are trying to find the endpoint when given the midpoint and one point, what would the new formula be? Manipulate the formula using skills for solving literal equations. How would you find LaTeX: x_2\:\:\:or\:\:\:y_2x 2 o r y 2? Use LaTeX: x_m\:\:and\:\:\:\:y_mx m a n d y mto notate the midpoints. Remember the original midpoint formula is LaTeX: \left(\frac{x_1+\:x_2}{2},\:\:\frac{y_{1\:}+y_2}{2}\right)\:=\:\left(x_m,\:y_m\right)

User Daneye
by
6.1k points

1 Answer

6 votes

Answer:


(x_2,y_2) = (2x_m - x_1 ,2y_m - y_1 )

Explanation:

Given


\left((x_1+\:x_2)/(2),\:\:(y_(1\:)+y_2)/(2)\right)\:=\:\left(x_m,\:y_m\right)

Required

Determine x2, y2

Start by splitting the expression


x_m = \left((x_1+\:x_2)/(2)) and
y_m = ((y_(1\:)+y_2)/(2))

Solving for x2 in
x_m = \left((x_1+\:x_2)/(2))

Multiply through by 2


2 * x_m = (x_1 + x_2)/(2) * 2


2x_m = x_1 + x_2

Make x2 the subject;


x_2 = 2x_m - x_1

Similarly:


y_m = ((y_(1\:)+y_2)/(2))

Multiply through by 2


2 * y_m = (y_1 + y_2)/(2) * 2


2y_m = y_1 + y_2

Make y2 the subject;


y_2 = 2y_m - y_1

Hence:


(x_2,y_2) = (2x_m - x_1 ,2y_m - y_1 )

User Arleny
by
5.7k points